Analysis of independent curriculum implementation problematic in elementary school: a case study in palembang city - Afandi, Muhamad; Baiti, Masnun; Purnamasari, Dwi; Sal Sal Bella, Nadia; Swantintrina, Swantintrina; Bujuri, Dian Andesta (Prodi PGSD FKIP Universitas Islam Sultan Agung, 2025)
The implementation of the independent curriculum has experienced various problems at the elementary education level. This study analyzes and describes the problems of implementing the Independent Curriculum at the elementary school level. This study uses a qualitative research method with a case study type. The subjects of this research were the headmaster and teachers at the lower and high-grade levels at Islamic Elementary School. The data collection techniques used were interviews, observation, and documentation. Data were analyzed using an interactive model. The validity of the data was tested by technique and source triangulation. The results of the study were obtained first, teachers experienced various problems in implementing the independent curriculum such as not understanding the independent curriculum comprehensively and the concept of differentiated learning; difficulty in designing learning; stuttering in using and developing teaching modules; and difficulty in implementing project-based learning which aims to strengthen the Pancasila and Rahmatan Lil'alamin Student Profile. Second, the factors causing these problems are the lack of understanding of teachers regarding the independent curriculum and the lack of training related to the independent curriculum. The majority of teachers have never attended training related to the implementation of the independent curriculum. Third, the efforts made by teachers are to look for references related to the concept of the independent curriculum and study it independently or discuss it with fellow teachers, and participate in training activity. This research proves that teachers must be equipped with maximum competence before implementing a curriculum.